Пошаговое объяснение:
1. 3(х+3)-3(4-х)-х-3 = 3x + 9 - 12 + 3x - x - 3 = 5x - 6
2. 3(х+5)-(4-х)-(1+3)х-3 = 3x + 15 - 4 + x - 4x - 3 = 8
3. 2(х+4)-3(2-х)-х-4 = 2x + 8 - 6 + 3x - x - 4 = 4x - 2
4. х+1-5(2-х)-(5+1)х-5 = x + 1 - 10 + 5x - 6x - 5 = -14
5. х+3-(2-х)-х-4 = x + 3 - 2 + x - x - 4 = x - 3
6. 4(х+3)-(5-х)-х-4 = 4x + 12 - 5 + x - x - 4 = 4x + 3
7. 3(х+3)-4(1-х)-(4+3)х-1 = 3x + 9 - 4 + 4x - 7x - 1 = 4
8. 5(х+5)-3(3-х)-х-3 = 5x + 25 - 9 + 3x - x - 3 = 7x + 13
9. 2(х+2) – 5(2-х)-(5+2)х-1 = 2x + 4 - 10 + 5x - 7x - 1 = -7
10. 2(х+4)-4(5-х)-(4+2)х-3 = 2x + 8 - 20 + 4x - 6x - 3 = -15
х= -42:14
х=3
2х-16=0
2х=16
х=16:2
Х=8
8х-17=23
8х=23+17
8х=40
Х=40:8
Х=5
5х=210+12х
5х-12х=210
-7х=210
Х=-210:7
Х= - 30
5х+21=3х+25
5х-3х=25-21
2х=4
х=4:2
Х=2
17-3х+7х=31-2х+10
-3х+7х+2х=31+10-17
-6х=24
Х=-24:6
Х=-4
2х-12=2(10-7х)
2х-12=20-14х
2х+14х=20+12
16х=32
Х=32:16
Х=2
5х-12-2(х-1)=3(5-2х)+4
5х-12-2х+2=15-6х+4
5х-2х+6х=15+4+12-2
9х=29
Х=29:9 может ошибка в условии?
14+х=2
Х=14:2
Х=7
2х+х-16=2
3х-16=2
3х=16+2
3х=18
х=18:3
х=6
8-17х=25
-17х=25-8
-17х=17
Х= -17:17
Х= -1
5-х=20+2х
-х-2х=20-5
-3х=15
Х=-15:3
Х= -3
Х+21=3-5х
Х+5х=3-21
6х=-18
Х= -18:6
Х=-3
17х-3+х=12-2х+5
17х+х+2х=12+5+3
20х=20
х=20:20
х=1
2(х-12)=210-7х
2х-24=210-7х
2х+7х=210+24
9х=234
х=234:9
х=26